Uji Patogenisitas Isolat Colletotrichum sp. Asal Bawang Merah (Allium ascalonicum) Terhadap Perkembangan Penyakit Antraknos Pada Varietas Cabai - Eli Korlina; Ineu Sulastrini; Neni Gunaeni (UIN Sunan Gunung Djati Bandung, 2023)
One of the main diseases in chili (Capsicum annuum) that can attack the fruit is anthracnose. The cause of this disease is caused by the fungus Colletotrichum spp. which can reduce production. In chili plants centers, farmers often intercrop it with shallots. Therefore, shallots can also be affected by anthracnose disease. This study aims to determine the pathogenicity of anthracnose isolates from shallots against infection by chili on a laboratory scale. The study was conducted at the Mycology Laboratory of the Indonesian Vegetables Research Institute (IVEGRI) in January 2020. The experiment used three shallot anthracnose isolates from Cipanas, Rancaekek and Lembang, also using three varieties of chili namely Kencana, Pilar, and Castillo. The results of the pathogenicity test showed that the Colletotrichum sp. isolate from shallots from Lembang, Cipanas, and Rancaekek could potentially cause anthracnose symptoms in chili with the highest lesions in Pilar varieties (1.61 cm) and the lowest in Kencana varieties (0.78 cm). Meanwhile, from the three sources of shallot isolates, whose incubation period is the fastest and the symptoms are always present in the inoculated chilies is Colletotrichum sp. isolate from Rancaekek.